A Secured Cloud Environment with User Validation Method for Data Communication - Gadde Swetha, K. Santhi Sri, D. Anveshini, P. Sandhya Krishna (International Journal of Advanced Science and Technology, 2020)
Cloud computing causes cloud users to give administrations at reduced expenses. Security is considered as the most significant boundary for utilizing cloud administrations. While a portion of the security concerns are not new, they are available in existing models, for instance, server downtime, loss of information, and secret key limitations. Cloud computing (CC) gained a widespread acceptance as a paradigm of computing. The main aim of CC is to reduce the need for customers’ investment in new hardware or software by offering flexible cloud services, with a user reaping the benefits of the pay per use approach. Security and privacy is the significant deterrent in cloud computing i.e. confidentiality, integrity, and availability of information. Importantly, data security is the major challenge of cloud computing. Encryption is an outstanding innovation for ensuring sensitive information. To reduce such issues the proposed work uses Quick User Authentication (QUA) model which is used to reduce the maximum of the security threats in the cloud. It is also used to increase the efficiency of the system by reducing the time and improving the performance.